Compact Dual-Frequency Slot Antenna for C-Band Applications Based on Substrate Integrate Waveguide - Keriee, Hussam; Essa, Eman Hassan; Mahdi, Haider S.; Nayyef, Nawres Abbas (IAES Indonesian Section, 2023)
This paper provides a compact substrate-integrated waveguide-based dual-frequency H-fractal slot antenna for the C-band (SIW). From the view of fractal slot antenna, two H-fractal slot shaped elements with 3rd iteration are used to cut currents in two TE modes, which leads to dual-frequency performance and reduces the size. The antenna operating at dual frequency of 4 GHz and 5.7 GHz with gain greater than 5 dB is designed and fabricated. Measured and simulated response of the antenna are introduced as well. The responses showed that the proposed antenna achieved stable dual-frequency performance with total size of 23 × 11 mm², which may be applied for C-band communication systems. The proposed antenna was simulated, analysed, and optimized using computer simulation technology (CST) software.